2011
DOI: 10.1590/s0103-50532011000700023
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical behavior of copper in drinking water: evaluation of dissolution process at low anodic overpotential

Abstract: O comportamento eletroquímico do cobre em água potável foi estudado por polarização potenciodinâmica e espectroscopia de impedância eletroquímica em até quatro dias depois de imersão em condições hidrodinâmicas diferentes. Os resultados de impedância foram interpretados usando modelos de circuito equivalente, os quais mostraram um aumento da espessura do filme com o tempo, que impede a difusão de espécies de cobre através da camada de óxido de cobre formada. Essa camada de óxido é maior em condição de estagnaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The oxide layer structure and composition cannot be derived from the XPS results presented, as it is not possible to distinguish between copper products using only the photoemission peak, being necessary to resort to the Auger peaks, which not included in their work . Rios et al . observed three time constants in much shorter immersion times and assigned the additional time constant, at higher frequencies, to the oxide layer on the surface, being the medium and low frequency time constants related to the copper corrosion mechanism already described.…”
Section: Understanding Eis In Cultural Heritagementioning
confidence: 97%
“…The oxide layer structure and composition cannot be derived from the XPS results presented, as it is not possible to distinguish between copper products using only the photoemission peak, being necessary to resort to the Auger peaks, which not included in their work . Rios et al . observed three time constants in much shorter immersion times and assigned the additional time constant, at higher frequencies, to the oxide layer on the surface, being the medium and low frequency time constants related to the copper corrosion mechanism already described.…”
Section: Understanding Eis In Cultural Heritagementioning
confidence: 97%
“…Copper, when exposed to neutral or slightly alkaline water, is known to develop a protective oxide layer. This protective layer comprises of cuprous species with other copper products like cupric oxide, cupric hydroxide and possibly cupric carbonate [7]. Grazing angle XRD performed on OFE copper as well as "BVAg-8 braze filler" specimens, exposed to stagnant process water, demonstrated that the surface film was comprised of Cu 2 O and CuO, as shown in Fig.…”
Section: Immersion Testsmentioning
confidence: 92%
“…However, with further exposure the conductivity of process water used in "flowing condition" recorded much larger increase with respect to its counterpart used in "stagnant condition. Possible contributing factors for the increase in water conductivity are believed to be increase in dissolved oxygen and carbon dioxide content and release of copper species from the oxides [7,8].…”
Section: Immersion Testsmentioning
confidence: 99%
See 2 more Smart Citations